Measles Immunoglobulin G Positivity and Associated Factors Among Suspected Cases in Three Selected Zambian Provinces: A Bayesian Logistic Regression Study - Priscilla Nkonde Gardner; Victor Daka; Paul Simusika; Walter Azibadighi; Charles Chileshe; Leah Kamulaza; Davie Simwaba; Roma Chilengi (Tropical Medicine and Infectious Disease, 2026)
Measles remains a public-health concern where immunity gaps and incomplete vaccination coverage persist. This study assessed household and geographic factors associated with laboratory-confirmed measles among suspected cases in three Zambian provinces. A prospective cross-sectional study was conducted during measles outbreaks in five selected districts across Luapula, Northern and Northwestern provinces. Suspected cases meeting the IDSR case definition were consecutively enrolled. Blood samples were collected, transported to the UTH Virology Laboratory, and tested using procured IgG test kits. Participant characteristics were summarised descriptively. Bayesian logistic regression estimated associations between laboratory-confirmed (IgG positive) measles and age, sex, vaccination status, household size and previous measles history, with province added in a second model. Results were reported as posterior odds ratios with 95% credible intervals. Among the 172 suspected cases, 45 (26.2%) were laboratory confirmed (IgG positive). Vaccination status was verified using caregiver-provided immunization cards; status was unknown for 110 (64.0%) participants (all of whom tested negative), reflecting missing vaccination documentation. Vaccinated participants had 93% lower adjusted odds of laboratory-confirmed measles than unvaccinated participants (adjusted posterior OR: 0.07, 95% CrI: 0.02–0.18). Adjusted posterior probabilities were consistently lower among vaccinated participants across all three provinces (34% to 49%) than among unvaccinated participants (86% to 92%). Age, sex and household size were not clearly associated with measles positivity. All four participants reporting a previous measles history tested positive, and the unadjusted association was significant using Fisher’s exact test (p = 0.004). Vaccination status was most strongly associated with laboratory-confirmed measles, with substantially lower adjusted odds among vaccinated participants. These findings reinforce the importance of measles vaccination in outbreak prevention and control.